2019
DOI: 10.1021/acs.macromol.8b02318
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Tunable Light-Induced Polymerization of Cyanoacrylates Using Photogenerated Amines

Abstract: Cyanoacrylate photopolymerization has already been described, but it generally requires the use of organometallic photoinitiators and highly reactive monomers, which often leads to photoinitiator−monomer mixtures with limited stability. In this work we report a method to tackle these limitations, which relies on the use of amines bearing photoremovable protecting groups as light-responsive nucleophilic cyanoacrylate initiators. By exploiting the versatility of amine photorelease strategies, we have developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The photorelease of diverse functional groups, including primary and secondary amines 794 , 805 , 809 , 810 , 812 (as carbamates), carboxylic acids, 295 , 794 , 795 , 798 , 802 , 804 , 806 808 alcohols 794 , 798 , 805 (as carbonic acid esters 794 or ethers 798 , 801 , 805 ), halogens, 798 hydroxylamines, 803 thiocarbamic acid, 799 thioacetic acid, 798 and thiols 800 ( Figure 15 ) from BODIPY-based PPGs, has been reported. The liberation efficiency of LGs correlated well with the p K a of their conjugate acids, 794 , 798 , 809 and the photoreaction quantum efficiency of unsubstituted BODIPYs (other than 1,3,5,7-tetramethyl derivatives) was moderate to low.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photorelease of diverse functional groups, including primary and secondary amines 794 , 805 , 809 , 810 , 812 (as carbamates), carboxylic acids, 295 , 794 , 795 , 798 , 802 , 804 , 806 808 alcohols 794 , 798 , 805 (as carbonic acid esters 794 or ethers 798 , 801 , 805 ), halogens, 798 hydroxylamines, 803 thiocarbamic acid, 799 thioacetic acid, 798 and thiols 800 ( Figure 15 ) from BODIPY-based PPGs, has been reported. The liberation efficiency of LGs correlated well with the p K a of their conjugate acids, 794 , 798 , 809 and the photoreaction quantum efficiency of unsubstituted BODIPYs (other than 1,3,5,7-tetramethyl derivatives) was moderate to low.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“… 804 , 806 Sebastián and co-workers used a meso -methyl BODIPY-caged diethylamine as an organic light-responsive nucleophilic cyanoacrylate initiator capable of fast on-demand photocuring of commercial formulations of various cyanoacrylates including biologically-relevant long alkyl chain monomers. 810 Klán and co-workers reported that controlled photorelease of alkynoic acids was followed by efficient decarboxylation, giving terminal alkynes that could subsequently undergo Cu I -catalyzed azide/alkyne cycloaddition reactions. 802 Similarly, Truong and co-workers developed a phototriggered thiol-propiolate addition that is initiated by uncaging methyl-3-mercaptopropionate.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“…To assess the efficacy of cyanoacrylate photopolymerization with ferrocene derivatives, calorimetric measurements were performed to enable simple, fast and repetitive in situ analysis for multiple monomer-photoinitiator combinations. 28 In these experiments very small volumes (100 μL) of rather diluted metallocene solutions in liquid cyanoacrylate (typically, 0.5 × 10 −3 M) were irradiated with blue light (λ exc = 420 nm), and the changes in temperature arising from exothermic CA polymerization were monitored. The time at which each sample reached half of the overall thermal increase associated with polymer curing (t photo ) was then taken to quantify photopolymerization efficiency, which gives comparable results to other analysis methods (e.g., viscosity or IR measurements (Figure S4)).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Cyanoacrylate derivatives are of industrial interest being subunits used to build many adhesives and polymeric materials (Faggi et al, 2019). They are also considered important intermediate precursors for the synthesis of different heterocyclic derivatives, see for example Qian et al (2018), and as nitrile-activated species in bioreduction reactions (Brenna et al, 2013(Brenna et al, , 2015Kong et al, 2016) among others.…”
Section: Chemical Contextmentioning
confidence: 99%